CBS News/New York Times Election Surveys, 1980 ([Verlag nicht ermittelbar], 1984)
The New York Times and CBS News were equal partners in a series of election surveys covering the 1980 election year. The content of this data collection generally concerns the presidential preference of respondents, their reasons for choosing a particular candidate, and their reactions to political and social issues of the campaign. There are 28 datasets in the collection, which fall into three categories: national monthly surveys, primary day surveys, and the election day survey. Parts 1-12 contain national monthly surveys that were conducted by telephone, with approximately 1,500 randomly selected adults in each. Surveys were conducted in January, February, March, April, June, August, September, and October. Two telephone surveys were conducted in September, a pre-debate survey and a post-debate survey. Also, two surveys were conducted in October. A post-election survey was conducted in the days following the election. For the post-election survey, the respondents in Part 11, October Pre-Election National Interviews, were reinterviewed. The post-election survey is released as a panel file and incorporates Part 11 responses as well. Parts 13-27 contain primary day surveys that were conducted in 11 states on the day of the primary at the polling place among a random sample of people who had just voted in either the Democratic or Republican presidential primaries. The questionnaires were self-administered. Surveys were conducted in the following states: New Hampshire, Massachusetts, Florida, Illinois, New York, Wisconsin, Pennsylvania, California, New Jersey, and Ohio. There are separate data files for the Democratic and Republican primaries in New Hampshire, Massachusetts, Illinois, Wisconsin, and Pennsylvania. Demographic information including age, sex, income, race, ethnicity, and occupation is provided for all respondents in Parts 1-27. Part 28 contains a survey conducted on the day of the presidential election. A national sample of voters was administered a questionnaire similar to those given on primary day. Selected voters were asked for whom they had voted and why. Information on time of voting and respondent's sex and race was filled out by the interviewer.